Identification of Pests and Diseases on Anthurium Plants (Anthurium andraeanum) in Sewu Kembang Tourism Village, Karanganyar - Nur Rokhimah Hanik; Rohmad Faoji (Jurnal Biologi Tropis, 2021)
Anthurium ornamental plants are currently very popular among ornamental plant lovers, both from the charm of the type and color and the high price. Although pests and diseases in anthurium are not very disturbing, if left unchecked it will greatly interfere with the beauty, inhibit growth and be detrimental to collectors and sellers/entrepreneurs of these ornamental plants. The purpose of this study was to determine the types of pests and diseases that attack anthurium plants. This research was carried out in the Sewu Kembang Nglurah Tourism Village, Tawangmangu Regency, Karanganyar Regency, for 30 days from Saturday, September 4 to October 3, 2021. This study used 20 samples of Anthurium plants. The tools used were cellphone cameras and stationery. The variables that will be observed are pests and diseases that attack Anthurium. This research used observation and interview methode, the data obtained were analyzed by qualitative descriptive. The results of this study found several pests and diseases on anthurium plants that caused the plant leaves and flowers to have holes, shriveled, yellowed spots, slimy, and caused stunted growth. The pests found were caterpillars and snails, while the diseases included fungus, chlorisis, leaf rust, anthracnose, curly leaves, and burnt leaves.